Direct sampling mass spectrometry for clinical analysis. Issue 4 (6th December 2018) - Pu, Fan; Chiang, Spencer; Zhang, Wenpeng; Ouyang, Zheng
Abstract : Direct sampling mass spectrometry enables high-performance clinical analysis, such as imaging, drug monitoring and point-of-care testing. Abstract : Direct sampling mass spectrometry (MS) has been advancing aggressively, showing immense potential in translating MS into the clinical field. Unlike traditional MS analysis involving extensive sample preparation and chromatographic separation, quick and simple procedures with minimal sample pretreatment or purification became available with direct sampling. An overview of the development in this field is provided, including some representative ambient ionization and fast extraction methods. Quantitative applications of these methods are emphasized and their efficacy are highlighted from a clinical aspect; non-quantitative applications in clinical analysis are also discussed. This review also discusses the integration of direct sampling MS with miniature mass spectrometers and its future outlook as an emerging clinical tool for point-of-care analysis.